Longitudinal Brain Magnetic Resonance Imaging CO2 Stress Testing in Individual Adolescent Sports-Related Concussion Patients: A Pilot Study - Mutch, W. Alan C.; Ellis, Michael J.; Ryner, Lawrence N.; Morissette, Marc P.; Pries, Philip J.; Dufault, Brenden; Essig, Marco; Mikulis, David J.; Duffin, James; Fisher, Joseph A. (Frontiers in Neurology, 2016)
Background: Advanced neuroimaging studies in concussion have been limited to detecting group differences between concussion patients and healthy controls. In this small pilot study we used brain magnetic resonance imaging (MRI) CO2 stress testing to longitudinally assess cerebrovascular responsiveness (CVR) in individual sports-related concussion (SRC) patients. Methods: Six SRC patients (3 male: 3 female; mean age= 15.7, range 15-17 years) underwent longitudinal brain MRI CO2 stress testing using blood oxygen level-dependent (BOLD) MRI and model-based prospective end-tidal CO2 targeting under isoxic conditions. First level and second level comparisons were undertaken using statistical parametric mapping to score the scans and compare them to an atlas of 24 healthy control subjects. Results: All tests were well tolerated and without any serious adverse events. Anatomical MRI was normal in all study participants. The CO2 stimulus was consistent between the SRC patients and control subjects and within SRC patients across the longitudinal study. Individual SRC patients demonstrated both quantitative and qualitative patient-specific alterations in CVR (p<0.005) that correlated strongly with clinical findings, and that persisted beyond clinical recovery. Conclusions: Standardized brain MRI CO2 stress testing is capable of providing a longitudinal assessment of CVR in individual SRC patients. Consequently, larger prospective studies are needed to examine the utility of brain MRI CO2 stress testing as a clinical tool to help guide the evaluation, classification, and longitudinal management of SRC patients.